Correlation between forkhead box P3 (rs3761548) gene polymorphism and serum interleukin13 as biomarkers of severity in Egyptian allergic conjunctivitis: a retrospective study - Boghdady, Wesam A.; Khairy, Marwa A.; Ali, Ali G.; El Shahawy, Alia A.; Abdelaziz, Eman A.; El Shahawy, Aya A.; Kamel, Fatma Z. (Frontiers in Allergy, 2024)
IntroductionThe genetic variants that alter human Forkhead Box P3 (FOXP3) function may have a part in the establishment of allergic conjunctivitis. Our study aimed to evaluate the FOXP3 polymorphism, serum interleukin13 (IL13) and total immunoglobulin E (IgE) levels in allergic conjunctivitis and assess their role as biomarkers for allergic conjunctivitis risk and severity.MethodsThis study included 52 cases and 52 controls. Blood samples were taken from allergic conjunctivitis patients and controls for total IgE, IL13 measurement and detection of FOXP3 (rs3761548) gene polymorphism.ResultsThere was a statistically significant difference between the allergic conjunctivitis group and healthy control group regarding FOXP3 (rs3761548) polymorphism with those have AA genotype are 12 times at risk for allergic conjunctivitis and A allele increases the risk of allergic conjunctivitis by about 4 times. There was statistically significant difference between mild/moderate and severe allergic conjunctivitis regarding FOXP3 (rs3761548) polymorphism with those have AA genotype are 53 times at risk for severe allergic conjunctivitis and A allele increases the risk of severe allergic conjunctivitis by about 6 times. Also, there was a significantly higher value of total IgE IU/ml, IL13 Pg/ml value in severe allergic conjunctivitis compared to moderate/mild allergic conjunctivitis. The best cutoff values of total IgE and serum IL13 for detecting the severity of allergic conjunctivitis were ≥320 IU/ml and ≥40 Pg/ml and the area under the curve were 0.89 and 0.95 respectively.ConclusionThe research significantly contributes to find correlation of FOXP3 polymorphism, total IgE and IL13 with risk and severity of allergic conjunctivitis which are limited in the literature on the perceived value relevance of FOXP3 polymorphism in allergic conjunctivitis risk and severity.